META-ANALISIS: PRAKTIKALITAS BOOKLET UNTUK MEDIA PEMBELAJARAN BIOLOGI SMA/MA - Ramadhani Trivina Dewi; Zulyusri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the importance of utilizing practical learning resources to support the biology learning process in senior high schools (SMA/MA). As a learning medium, the booklet has significant potential to support instruction, as it is frequently developed for its ability to present material in a concise, systematic, and engaging manner. This study aimed to analyze the practicality of booklets used to support biology learning in SMA/MA, based on previously published research findings. A meta-analysis method was employed, examining ten relevant studies regarding booklet development in biology education. Data were gathered through article searches on Google Scholar and analyzed using quantitative descriptive methods. The results indicate that the highest practicality score based on teacher assessments was 100% and the lowest was 83.48%, while the highest score based on student assessments was 94.59% and the lowest was 84.60%. Average calculations reveal a practicality score of 90.71% based on teacher assessments and 89.89% based on student assessments. Both figures fall into the "highly practical" category. These findings indicate that booklets meet the criteria for use as biology learning media in SMA/MA, as they are easy to use, facilitate material delivery, enhance student learning independence, and contribute to a more effective and efficient learning process.